Död ved i ett referensvattendrag - Andersson, Andreas (2015)
The purpose with this study is to find out how much dead wood we can expect us to find in a Russian reference river and compare with studies from Swedish streams. Dead wood are an important structure for the biodiversity in forest streams, studies have shown that population of trout can increase with up to 300 % when the amount of dead wood are increasing from 0 to 8 – 16 LWD (Large woody debris)/100 m2. Dead wood are also an important structure for the stream character, formations of dams and pools which are important habitats and reproduction areas for salmon and brown trout. The study where taken place in tributaries to the Russian river Varzuga in the North West part of Russia outside Murmansk. Varzuga has low impact of human activity and is considered to be a reference river to rivers in northern Sweden. The sample areas where between 22.5 up to 109 m2, in the stream where all dead wood classified as LWD (length over one meter long and a diameter larger than teen cm) reported as cubic meters per hectare. In order to estimate the volume of forest in associated riparian zone, measurements of five thirty meter long and two meter wide samples on both sides of the stream were collected. This study shows that the average amount of dead wood in streams in my study area where between 5.5 and 18.7 m3 /ha and the average log was 2.2 meter long and hade a volume of 0.03 m3. In the associated riparian zone the average volume was 74.4 m3 per hectare and the average volume of dead wood was 11.8 m3 per hectare. Measures of LWD showed the average amount where between 2.6 and 5,9 LWD/100 m2 stream. Compared with results from the Swedish Electrofishing Register, in 4382 Swedish forest streams LWD was quantified as 50 cm long and a diameter of 10 cm or more, the average amount of LWD was 1.0 LWD/100 m stream section. To find out what a suitable amount of dead wood in Swedish forest streams more studies are needed in the future.